THE MAGNITUDE OF FINANCIAL IMBALANCES CORRECTION AND THE PROBLEM OF RESTORING GROWTH - Koziuk, Viktor (Journal of European Economy, 2019)
EMU imbalances correction sparked active discussions on choosing the optimal policy for mitigating risks of divergence and restoring competitiveness. Concentration on balance of payments is within the framework of simultaneously solving the problem of external imbalance, capital outflow, restoring growth, and preventing the opposing vectors of trajectory of the real effective exchange rates. However, overcoming the crisis consequences requires a wider approach to how the imbalances correction contributes to the growth recovery. Theoretically, the rate of post-crisis growth recovery should correspond with the variables that constitute imbalances correction. Based on regression analysis, it is clear that such hypothesis is proved only partially. Growth is more likely to recover if there is a more substantial correction of current account and credit market cleaning-up, whereas the correction on real estate market is not as effective. At the same time, real disposable income correction is likely to negatively influence the growth recovery. Nevertheless, this doesn’t mean that internal devaluation shouldn’t be utilized as an option during macroeconomic adjustment. It should occur with credit market cleaning-up. Fiscal space is crucial here, as it determines the credibility of fiscal policy devoted to mitigation of accumulated household sector debt burden. The reaction to the financial cycle is a fundamentally important element of macroeconomic management in the monetary union in regards to the macroeconomic design of integration zone. JEL: F32, F41, F45.